Analysis of Byzantium Apparel's Marketing Strategy in Increasing Competitiveness in the Sports Apparel Market - antono, muh yopan; hartono, mugiyo (Journal of Physical Education and Sports, 2025)
Byzantium Apparel is a growing local business engaged in the sportswear industry, facing intense competition and rapidly changing market dynamics. This research aims to analyze the marketing strategy of Byzantium Apparel using the SWOT framework to identify strengths, weaknesses, opportunities, and threats, as well as to formulate recommendations for business development. A qualitative descriptive method was applied through interviews with the business owner, employees, and selected customers, supported by direct observation and document analysis. The findings reveal that Byzantium Apparel has strong advantages in building customer loyalty through community-based marketing, competitive pricing, and active digital promotion via social media platforms. However, weaknesses such as limited human resources for innovative content creation, inconsistent promotional scheduling, and reliance on third-party distribution channels were identified. The study also highlights significant opportunities arising from the growth of sports communities, digital technology advancements, and increasing health-conscious lifestyles. Nonetheless, threats from larger competitors, shifting social media algorithms, and the risk of imitation remain challenges. This research contributes to marketing knowledge, particularly for small businesses in the sportswear sector, by providing practical insights into adaptive, community-oriented, and digital-driven marketing strategies.